Ultrasonic-assisted fabrication of polyvinyl chloride/mixed graphene-carbon nanotube nanocomposites as a selective Ag+ ionic sensor. (July 2019) - Hussein, Mahmoud A; Alam, MM; Asiri, Abdullah M; Al-amshany, Zahra M; Hajeeassa, Khdejah S; Rahman, Mohammed M
Polyvinyl chloride/mixed graphene-carbon nanotube nanocomposites have been fabricated in the form of (PVC/MG-CNTsa-e ) via simple dissolution method with the help of ultrasonic assistance. First, mixed G:CNTs ratio (50:50) wt by wt was prepared. Then, different loadings of that mixed G/CNTs ratio (2, 5, 10, 20, and 30 wt %) were added to the PVC polymer matrix. The fabricated PVC/MG-CNTsa-e nanocomposites were characterized by different techniques including: FT-IR, XRD, SEM, TEM and thermal analyses. The perception found in the FT-IR results of PVC nanocomposites confirm the introduction of mixed G/CNTs nanoparticles in the PVC polymer matrix. The mixed G/CNTs were stimulated in highly regular order in the PVC film and its crystallinity was significantly improved. The thermal property of pure PVC polymer matrix was noted to be highly improved by combining the mixed G/CNTs in the form of nanocomposites. CDT max for all the samples were nearly similar and appeared in the same range of 270–305℃. Here, a potential Ag + ionic sensor has been fabricated based on the glassy carbon electrode coated by PVC/MG-CNT NCs to make a thin layer as working electrode probe. The slope of the calibration curve plotted as current versus the concentration of Ag + ion was used to calculate the sensitivity (6.4241 µAµM −1 cm −2 ) by considering the active surface area of the sensor probe. The current observation based on Ag + ionic concentration is found to be linear over the linear dynamic range, where the detection limit (DL = 14.78 ± 0.74 pM) is measured by considering the signal to noise ratio at 3. Considering the application feature of Ag + ion sensor, the proposed sensor was demonstrated to have good reproducibility and reliability for the sensor application through the determination of toxins in environmental and healthcare fields at broad scales.